2005
DOI: 10.1128/jvi.79.15.9439-9448.2005
|View full text |Cite
|
Sign up to set email alerts
|

Variant-Specific Tropism of Human Herpesvirus 6 in Human Astrocytes

Abstract: Though first described as a lymphotropic virus, human herpesvirus 6 (HHV-6) is highly neuropathogenic. Two viral variants are known: HHV-6A and HHV-6B. Both variants can infect glial cells and have been differentially associated with central nervous system diseases, suggesting an HHV-6 variant-specific tropism for glial cell subtypes. We have performed infections with both viral variants in human progenitor-derived astrocytes (HPDA) and monitored infected cell cultures for cytopathic effect (CPE), intra-and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
77
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(79 citation statements)
references
References 43 publications
1
77
1
Order By: Relevance
“…To date, no evidence of productive HHV-6B infection has been obtained for neural stem cells, astrocytes and oligodendrocytes, [67][68][69] suggesting that CNS reactivation depends on systemic HHV-6 reactivation. Autopsy studies of patients who died with HHV-6 encephalitis have shown the hippocampus has strong reactivity against HHV-6, 9,70 and HHV-6 has displayed tropism for astrocytes in the hippocampus.…”
Section: Pathogenesis: We Do Not Know How Hhv-6 Contributes To Cns DImentioning
confidence: 99%
“…To date, no evidence of productive HHV-6B infection has been obtained for neural stem cells, astrocytes and oligodendrocytes, [67][68][69] suggesting that CNS reactivation depends on systemic HHV-6 reactivation. Autopsy studies of patients who died with HHV-6 encephalitis have shown the hippocampus has strong reactivity against HHV-6, 9,70 and HHV-6 has displayed tropism for astrocytes in the hippocampus.…”
Section: Pathogenesis: We Do Not Know How Hhv-6 Contributes To Cns DImentioning
confidence: 99%
“…As HHV-6 is known to be neurotropic in humans and to infect both human astrocytes and oligodendrocytes (22)(23)(24)(25), we next analyzed the permissiveness of primary brain glial cultures, which mostly contain astrocytes and, to a lesser extent, oligodendrocytes and microglial cells (data not shown), to HHV-6 infection. These cultures were obtained from either CD46-cyt1 mice, expressing the cyt1 isoform of CD46, or wild-type littermate con-trols (Fig.…”
Section: Infection Of Cd46-transfected Murine Lymphocyte Lines With Hmentioning
confidence: 99%
“…CD46 expression in humans is ubiquitous (19); therefore, it provides a wide range of potentially susceptible cell types for HHV-6 infection. Although lymphocytes are known as the main target cells, several CNS cell types, including astrocytes and oligodendrocytes, have been successfully infected by HHV-6A and, with lower efficiency, by HHV-6B (20)(21)(22)(23)(24)(25)(26)(27). Recently, CD134 (OX40), a member of the tumor necrosis factor (TNF) receptor superfamily that was expressed on activated T lymphocytes, has been identified as a receptor molecule for HHV-6B (28).…”
mentioning
confidence: 99%
“…The four remaining peptides, 083s, 1017, 1106, and 1211s, have significant homology with HHV-7 (see Table S2). HHV-6A but not HHV-6B is characterized by neurotropism (2,21,33), and so it would be advantageous to have reagents to corroborate if relapses in diseases like MS are associated with immune responses to HHV-6A rather than HHV-6B, as suggested by Fogdell-Hahn et al (25). Sequence analysis of the 11 epitope peptides and cross-reactivity studies (Fig.…”
mentioning
confidence: 97%